Adaptation of the alimentary tract to feeding habits in four species of fish of the genus Channa - Gupta, M Das (Indian Journal of Fisheries, 2011)
The structure and morphometries of the alimentary canal of Channa orientalis,C. punctatus, C. striatus and C. marulius are described in relation to their foodand feeding habits. The general pattern of the alimentary canal was found tobe similar and of carnivorous type in the four species studied. C. striatus wasfound to be the most carnivorous as indicated by the structure and morphometriesof the alimentary canal and nature of gut content followed by C. marulius andC. orientalis was found to be the least carnivorous. Pattern of the mucosal foldsin the different regions of the alimentary canal showed inter and intra-specificvariations.